"This migrants' babble is not a German dialect!": The interaction of standard language ideology and 'us'/'them' dichotomies in the public discourse on a multiethnolect. (25th June 2015) - Wiese, Heike
Abstract This article investigates a public debate in Germany that put a special spotlight on the interaction of standard language ideologies with social dichotomies, centering on the question of whether Kiezdeutsch, a new way of speaking in multilingual urban neighbourhoods, is a legitimate German dialect. Based on a corpus of emails and postings to media websites, I analyse central topoi in this debate and an underlying narrative on language and identity. Central elements of this narrative are claims of cultural elevation and cultural unity for an idealised standard language 'High German', a view of German dialects as part of a national folk culture, and the construction of an exclusive in-group of 'German' speakers who own this language and its dialects. The narrative provides a potent conceptual frame for the Othering of Kiezdeutsch and its speakers, and for the projection of social and sometimes racist deliminations onto the linguistic plane. (Standard language ideology, Kiezdeutsch, dialect, public discourse, Othering, racism by proxy)*